Analysis Of The Influence Of Brand Awareness, Brand Associations, And Lifestyle On Purchase Decision Process iPhone (Consumer Survey in Padang City) - Aswin, Ullya Rahmi; Hidayat, Danny; Gustina, Leni (Fakultas Ekonomi Universitas Andalas, 2023)
This study aims to determine the influence of Brand Awareness, Brand Association, and Lifestyle in the iPhone Purchase Decision Process in Padang City. The data analysis method used is Validity Test, Reliability Test, Multiple Regression Analysis, Hypothesis Test consists of Partial Test (t Statistical Test), Simultaneous Test (F Statistical Test), and Determination Coefficient Test (R2). The work was carried out using SPSS 17. The data used are primary data and secondary data. This study used a sample of 100 research respondents. The results of this study indicate that data analysis using the multiple linear regression analysis method shows that Brand Association and Lifestyle have a positive and significant effect on consumers' decision to buy an iPhone, while Brand Awareness has a positive but not significant effect on the consumer's decision process in buying an iPhone. Based on the t-test that the three most dominant variables influencing the decision process to purchase the hijab are Lifestyle (X3) with a t value of 0.532. Adjusted analysis of the coefficient of determination obtained an R2 value of 39.7%, which means that the dependent variable, namely the purchase decision process, can be explained by the independent variables, namely Brand Awareness, Brand Association and Lifestyle and the remaining 60.3% is not influenced by other variables. included in this research.